Verification of glutamate as the amino acid residue responsible for manganese ion preference in entamoeba histolytica choline kinase - Yee, Low Sin (Universiti Sains Malaysia, 2016)
Entamoeba histolytica is a parasitic protozoan that causes amoebiasis, a major public health problem in developing countries. Amoebiasis can be presented with no, mild, or severe symptoms such as abdominal pain, mild diarrhea, bloody diarrhea or severe colitis with tissue death and perforation. The plasma membrane of£. histolytica is important in its invasiveness and contact dependence cytotoxicity. The major component of its plasma membrane (60- 70%) is phospholipid. Phosphatidylcholine (PC) is one of the predominant phospholipids of the plasma membrane in E. histolytica. PC synthesis begins with phosphorylation of choline by choline kinase (CK). It is widely accepted that the CK of many organisms prefer Mg2+ as their cofactor for phosphorylation. However, previous studies showed an unusual preference of E. histolytica choline kinase (EhCK) towards Mn2+ ion. EhCK activity was shown to increase 24 folds in the presence of Mn2+. Based on the protein sequence alignment, three amino acid residues, including glutamate-100, were identified and predicted to be responsible for the preference of Mn2+ ion as a cofactor. The aim of this study was to validate the role of glutamate-100 in Mn2+ ion cofactor preference. Glutamate-100 was replaced with glutamine (E100Q) utilizing PCR site directed mutagenesis. Mutant EhCK-ElOOQ and wild type EhCK open reading frame (ORF) were respectively cloned into pGEX-RB vectors. The proteins were expressed and purified. Both of the proteins were used in the assay by employing pyruvate kinase-lactate dehydrogenase coupled spectrophotometric assay. Different Mn2+ concentrations were used in the assay in order to determine the Ko s. The Ko s for wild type EhCKand EhCK-ElOOQ were 10.5 mM and 9.14 mM, respectively. In conclusion, this study showed that the predicted amino acid glutamate-100 was not the specific amino acid residue that was responsible for the protein preference using Mn2+ as its cofactor. Further studies need to be carried out on other amino acid residues to identify the correct amino acid that actually plays the role in the Mn2' preference. This study lays the groundwork for future study on EhCK. inhibition.